PENGARUH SELF EFFICACY DAN DUKUNGAN TEMAN SEBAYA TERHADAP RESILIENSI AKADEMIK SISWA JURUSAN AKUNTANSI DI SMK SWASTA LAKSAMANA MARTADINATA - Roy Prayuda, Muhammad; Darma, Jufri; Thohiri, Roza; Dwi Putra, Pasca; Sriwedari, Tuti (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study examines the influence of self-efficacy and peer support on the academic resilience of Accounting students at SMK Swasta Laksamana Martadinata. Academic resilience is an essential factor that enables students to cope with academic challenges, while self-efficacy and peer support are considered important determinants in strengthening students' ability to adapt and persist in learning. The purpose of this study was to analyze the effect of self-efficacy and peer support on students' academic resilience. This research employed a quantitative approach using descriptive and verification methods. Data were collected through questionnaires administered to 55 students selected from the Accounting Department. The data were analyzed using the Structural Equation Modeling–Partial Least Squares (SEM-PLS) approach with SmartPLS 4. The findings indicate that self-efficacy has a positive and significant effect on academic resilience, with a path coefficient of 0.572 and a p-value of 0.000. Peer support also has a positive and significant effect on academic resilience, with a path coefficient of 0.256 and a p-value of 0.049. These results demonstrate that students with higher levels of self-efficacy and stronger peer support tend to exhibit better academic resilience when facing academic demands and learning difficulties. Therefore, enhancing students' confidence in their abilities and fostering supportive peer relationships are important strategies for improving academic resilience among vocational high school students.